2013
DOI: 10.1038/srep01426
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow-current-density and bias-field-free spin-transfer nano-oscillator

Abstract: The spin-transfer nano-oscillator (STNO) offers the possibility of using the transfer of spin angular momentum via spin-polarized currents to generate microwave signals. However, at present STNO microwave emission mainly relies on both large drive currents and external magnetic fields. These issues hinder the implementation of STNOs for practical applications in terms of power dissipation and size. Here, we report microwave measurements on STNOs built with MgO-based magnetic tunnel junctions having a planar po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
160
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(168 citation statements)
references
References 30 publications
5
160
0
Order By: Relevance
“…This structure was able to exhibit a reduced threshold current, a high power and a high Q factor. 28,29 It has been theoretically demonstrated that this configuration is capable of generating microwave signal in zero applied magnetic field by taking into account the field-like torque. 30 However, the dependence of oscillation behavior on the field-like torque still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This structure was able to exhibit a reduced threshold current, a high power and a high Q factor. 28,29 It has been theoretically demonstrated that this configuration is capable of generating microwave signal in zero applied magnetic field by taking into account the field-like torque. 30 However, the dependence of oscillation behavior on the field-like torque still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In the STO study of Zeng et al 45 , the minimum observed linewidth of the primary mode (corresponding to the N = 1 mode here) was on the order of 30 MHz, suggesting that detection could be realised for d up to ∼ 50 or 60 nm based on the ∆f values shown in Fig. 8.…”
Section: System Dependencies Of ∆Fmentioning
confidence: 54%
“…A spherical MNP of diameter 20 nm is located above the disc. The separation between the upper surface of the disc and the bottom surface of the MNP is denoted by d. The nanodisc approximates the CoFeB free layer of a STO shown recently to function under low injected current and without strong external magnetic fields 45 , properties which may be advantageous for low-power, portable diagnostics 24 . Indeed exploiting precession of out-of-plane moments in STOs offers excellent potential in terms of achieving low linewidth outputs 40,46,47 , something which is critical for distinguishing MNP-induced frequency changes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was found [7,8] that an STO with a perpendicularly magnetized free layer and an in-plane magnetized pinned layer [9][10][11][12][13][14] can achieve a large emission power of close to 1 µW. Therefore, this type of STO will be the model structure for practical STO applications.…”
mentioning
confidence: 99%